Pengaruh penambahan tepung kacang kedelai terhadap daya terima organoleptik dan proksimat pada mie instant buah naga - Rizkiya Nabila; Abdul Hadi (DAPU Aceh Publishing, 2025)
No matter your socioeconomic status, you're sure to find instant noodles on the menu. The Indonesian people have a strong preference for noodles. The World Instant Noodle Association (WINA) reports that, after only China and India, Indonesia has the highest demand for instant noodles globally. Noodles that are less harmful to the body have been the subject of several research and development initiatives. To make sure that noodles get all the nutrients they need, researchers are considering adding nutrient-rich soy bean flour. The research strategy used in this study is a non-factorial Completely Randomized Design (CRD) trial with three treatments and three iterations. Analysis of variance and Duncan's test for additional significance were used to those data. The addition of soy bean flour to dragon fruit instant noodles did not significantly alter their color, scent, taste, or texture, according to organoleptic test findings (P Value> 0.05). Adding soy bean flour to dragon fruit instant noodles did not significantly change their protein or carbohydrate content in the proximate test. The actual impact on the contents of water, ash, fat, and fiber is shown by a P Value less than 0.05. Dragon fruit instant noodles preserved using soy bean flour retain all of their original color, flavor, fragrance, texture, protein, and carbohydrate content. The amounts of water, ash, fat, and fiber are all significantly altered, however.